2009
DOI: 10.1073/pnas.0811260106
|View full text |Cite
|
Sign up to set email alerts
|

Structural arrangement of the transmission interface in the antigen ABC transport complex TAP

Abstract: The transporter associated with antigen processing (TAP) represents a focal point in the immune recognition of virally or malignantly transformed cells by translocating proteasomal degradation products into the endoplasmic reticulum-lumen for loading of MHC class I molecules. Based on a number of experimental data and the homology to the bacterial ABC exporter Sav1866, we constructed a 3D structural model of the core TAP complex and used it to examine the interface between the transmembrane and nucleotide-bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
77
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(85 citation statements)
references
References 45 publications
7
77
1
Order By: Relevance
“…1E and F). Such extended α-helices are not found in the "importer" fold, suggesting that they might be directly related to the exporter type mechanism and, in some ABC exporters, they have been linked to recognition of a soluble transported substrate [49][50][51]. All together, the cytosolic protrusions of TMD helices generate four intracellular loops (IL1-IL4) that contain the so-called coupling helices.…”
Section: General Structural Features Of Abc Transportersmentioning
confidence: 99%
“…1E and F). Such extended α-helices are not found in the "importer" fold, suggesting that they might be directly related to the exporter type mechanism and, in some ABC exporters, they have been linked to recognition of a soluble transported substrate [49][50][51]. All together, the cytosolic protrusions of TMD helices generate four intracellular loops (IL1-IL4) that contain the so-called coupling helices.…”
Section: General Structural Features Of Abc Transportersmentioning
confidence: 99%
“…Recent structural characterization of several full prokaryotic ABC transporters (14,30) and of mouse P-glycoprotein (15) has revealed that four ICLs extend the helical structures of the transmembrane segments into the cytosol and contact the surface of NBDs to shape an MSD-NBD interface. Such an interface is predicted to transmit conformational changes between MSDs and NBDs, a fundamental aspect of the molecular mechanism employed by ABC transporters to couple substrate translocation with ATP binding/hydrolysis (9,10). In addition, the observation that, for ABC exporters, the second ICL of one MSD contacts the opposite NBD and ICL, suggests that the contacts engaged by ICLs may be important for the harmonized response of the two halves of the protein to such conformational changes.…”
Section: Discussionmentioning
confidence: 99%
“…This interface is thought to be essential in coupling the information of ATP binding and hydrolysis to ligand translocation, as shown by the studies conducted on the human TAP transporter (9) and on the yeast drug pump Pdr5 (10). However, despite the conserved nature of this interface, the precise mode of interaction differs according to the type of transport: in the bacterial importers BtuCD and ModBC, the ICL-NBD interface is composed entirely of interactions within the same half-transporter (11,12), whereas in the bacterial exporters Sav1866 and MsbA, the two halves of the transporter undergo domain swapping such that the ICLs of one polypeptide interact predominantly with the NBD of the opposite halftransporter (13,14).…”
mentioning
confidence: 99%
“…All structures share a conserved architectural arrangement with a core of 12 TM helices and two NBDs. An additional N-terminal domain (TMD0), most likely involved in regulatory functions only, is observed in several human homologues, especially within the ABCC subfamily but is also known from TAP1/TAP2 [24]. In each 'half transporter' (see Figure 3A), TM helices 2-6 are extended significantly beyond the membrane boundary with an average length of almost 70 Å.…”
Section: Abc Exportersmentioning
confidence: 99%